Compatibility of Crop Patterns with Climate Change for Irrigation Projects in Semi-Arid Regions: The Case Study of the Abu Ghraib Project in Iraq - Alsamarray, Rusul S.; Al-Khafaji, Mahmoud S.; Shemal, Khalid (Engineering, Technology & Applied Science Research, 2025)
The climate change has become a significant threat to the water security and agricultural productivity, particularly in arid and semi-arid regions. The overall aim of this paper is to demonstrate the compatibility of the current crop patterns with the climate change in the semi-arid areas, using the Abu Ghraib Irrigation Project (AGIP)- one of Iraq’s most significant irrigation projects- as a case study. The observed climate data from 1993 to 2023 were used to forecast the climate parameters for 2025–2075 under the Shared Socioeconomic Pathway (SSP) 2-4.5 scenario, utilizing the LARS-WG weather generator and the HadGEM3-GC31-LL model for RCP 5. The CROPWAT 8.0 model was employed to assess the crop water requirements, including the calculations of evapotranspiration and irrigation demands for the summer and winter cropping patterns based on the Penman–Monteith equation. The results indicate a consistent increase in both the maximum and minimum temperatures, accompanied by a slight decline in the annual precipitation. As a result, the Net Irrigation Water Requirements (NIWR) for most crops are projected to have increased by up to 80% by 2075 compared to the historical baselines. Crops, such as wheat, alfalfa, eggplant, and dry onion, exhibited high sensitivity to climatic changes, whereas others, like barley, cowpea, and spinach, demonstrated greater adaptability. The findings indicate that the current cropping patterns are not suitable for the future climate conditions. This highlights the need to modify the farming strategies by selecting drought-resistant crops and adopting modern irrigation techniques. The study also provides valuable information to help improve the water management and support the agriculture in dry and semi-dry regions.